Distribution and Seasonal Variation of Intertidal Bivalves on a Sandy Beach at Caimare Chico, Venezuela - Delgado, José; Reverol, Yinett; Godoy, Antonio; Severeyn, Héctor (Boletín del Centro de Investigaciones Biológicas)
We studied distribution and seasonal variation of intertidal bivalves on a sandy beach at Caimare Chico, Zulia State, Venezuela, from December 1995 to August 1996, during rainy and dry seasons. Samples were collected at lowest tide in water depths from 0.0 to 0.5 m, by using an Ekman dredge (0.022 m2). Twenty-four species, in 18 genera and 12 families were collected. The Shannon-Weaver Index (HÂ´) of species diversity varied from 0.24 to 1.50, evenness between 0.10 and 0.53, and MargalefÂ´s species richness (Dmg) from 1.34 to 2.89. The intertidal area was divided into three different zones according to species distribution and abundance. The first zone was characterized by Donax striatus, Tivela mactroides, Donax denticulatus, Strigilla pisiformis and Pteria colymbus, the second zone by Chione cancellata, Crassinella lunulata, Pitar dione, Macoma breviformis and Codakia orbicularis, and the third zone by Anadara braziliana and Macoma sp. The structure of this distribution occurred throughout the sampling period. Total rainy season abundance was lower than that recorded in the dry season.